2012
DOI: 10.1007/s11606-012-2284-1
|View full text |Cite
|
Sign up to set email alerts
|

Verbal and Physical Aggression Directed at Nursing Home Staff by Residents

Abstract: CONTEXT: Little research has been conducted on aggression directed at staff by nursing home residents. OBJECTIVE: To estimate the prevalence of resident-tostaff aggression (RSA) over a 2-week period. DESIGN: Prevalent cohort study. SETTING: Large urban nursing homes. PARTICIPANTS: Population-based sample of 1,552 residents (80 % of eligible residents) and 282 certified nursing assistants. MAIN OUTCOME MEASURES: Measures of resident characteristics and staff reports of physical, verbal, or sexual behaviors dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 49 publications
3
67
0
2
Order By: Relevance
“…There is also a small body of literature on the mistreatment of elderly residents by staff of nursing homes (Cohen, Halevy-Levin, Gagin, Priltuzky, & Friedman, 2010; Payne & Cikovic, 1994; Pillemer & Moore, 1989), and on aggressive behaviors experienced by family members and paid caregivers at the hands of older people with dementia (Finkel, Costa de Silva, Cohen, Miller, & Sartorius, 1997; Lachs et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a small body of literature on the mistreatment of elderly residents by staff of nursing homes (Cohen, Halevy-Levin, Gagin, Priltuzky, & Friedman, 2010; Payne & Cikovic, 1994; Pillemer & Moore, 1989), and on aggressive behaviors experienced by family members and paid caregivers at the hands of older people with dementia (Finkel, Costa de Silva, Cohen, Miller, & Sartorius, 1997; Lachs et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…However, there is mounting interest in R-REM, as indicated by a number of recent articles (Castle, 2012; Lachs et al, 2012; Pillemer et al, 2011; Ramirez et al, 2013; Rosen et al, 2008; Shinoda-Tagawa, Leonard, Pontikas, McDonough, Allen, & Dreyer, 2004; Teresi et al, 2013a, Teresi et al, 2013b). Such aggression has been found to be extensive (Pillemer et al, 2011; Shinoda-Tagawa et al, 2004) and can have both physical and psychological consequences for residents and staff (Cohen – Mansfield, Marx and Rosenthal, 1989; Rosen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature identified five major risk factors for the health of these workers. These factors are: (1) high physical demands [16; 17], (2) client assaults that put their mental and physical health at risk [18], (3) ethical suffering linked to a gap between the prescribed organization and the actual organization of tasks [19], (4) low social support and poor decision-making latitude [20], and (5) strong emotional demands and low recognition at work [21].…”
Section: Health Of Workers In the Home Support Sectormentioning
confidence: 99%
“…Although not as common, another form of abuse in institutional settings is staff-to-resident abuse (Pillemer & Moore, 1989). Finally, the phenomenon of resident-to-staff aggression has been studied recently (Lachs et al, 2013). In that study it was found that the prevalence of staff-reported physical and verbal aggression by residents directed toward staff was high, with 15.6% of residents reported to direct aggressive behavior toward staff, 8% of which was physical.…”
Section: Elder Abuse Research and Definitionsmentioning
confidence: 99%